JEAB Research Over Time: Species Used, Experimental Designs, Statistical Analyses, and Sex of Subjects - Zimmermann, Zachary J. (Behav Anal, 2015)
We examined the species used as subjects in every article published in the Journal of the Experimental Analysis of Behavior (JEAB) from 1958 through 2013. We also determined the sex of subjects in every article with human subjects (N = 524) and in an equal number of randomly selected articles with nonhuman subjects, as well as the general type of experimental designs used. Finally, the percentage of articles reporting an inferential statistic was determined at 5-year intervals. In all, 35,317 subjects were studied in 3,084 articles; pigeons ranked first and humans second in number used. Within-subject experimental designs were more popular than between-subjects designs regardless of whether human or nonhuman subjects were studied but were used in a higher percentage of articles with nonhumans (75.4 %) than in articles with humans (68.2 %). The percentage of articles reporting an inferential statistic has increased over time, and more than half of the articles published in 2005 and 2010 reported one. Researchers who publish in JEAB frequently depart from Skinner’s preferred research strategy, but it is not clear whether such departures are harmful. Finally, the sex of subjects was not reported in a sizable percentage of articles with both human and nonhuman subjects. This is an unfortunate oversight.